The virtues of language : history in language, linguistics, and texts : papers in memory of Thomas Frank - Stein, Dieter, 1946-; Sornicola, Rosanna, 1953-; Frank, Thomas, 1925-1990 (Amsterdam studies in the theory and history of linguistic science. Studies in the history of the language sciences ;, 1998)
The volume contains 13 specially written specialist articles on a wide range of subjects within the ambit of the history of the English language and prominent literary uses of it. In uniting linguistic and literary pursuits in a single volume, it follows the noble Neapolitan scholar's research interests, as well as representing topics that figure prominently in any comprehensive university course in English. Subjects range from the rise of the present progressive in the Anglo-Saxon Chronicle via issues in Medieval English, concepts of language inherent in the Early Modern English grammatical t.